The Handover and Performance Analysis of LTE Network with Traditional and SDN Approaches. (14th April 2022) - Emran, Muhammad; Thayananthan, Vijey; Umair, Muhammad; Kotuliak, Ivan; Qureshi, Muhammad Shuaib; Qureshi, Muhammad Bilal
Abstract : The mobility of user equipment (UE) in cellular network is a challenging issue in terms of its management. Current traditional handover in Long-Term Evolution (LTE) network is managed by evolved Node B or eNodeB (eNB) which is a decentralized solution. In contrast to existing technology, software defined network (SDN) has the capability of serving the packets of the switching equipment without involving the SDN controller except for the first one. We have proposed an SDN-based centralized solution for handover management in LTE network. Based on our solution, the handover is being managed by SDN controller which keeps track of the overall network management and dictates the flow entries to the OpenFlow switches in the network. In our testbed, two UEs are connected to two eNBs, and one of the UE performs a handover from one eNB to other eNB. It enhances the performance of the network in terms of reducing the delay while performing the handover and increasing the data rate of the running application. The initial delay will be bit higher due to the initial flow entry absence in the flow tables of the switches; later, the delay will be reduced. It is evident from the results that our approach keeps track of the overall network at centralized controller with improved performance.